Власть и тело: история любви - Бурлачук, В. (Социология: теория, методы, маркетинг, 2006)
Resting on fundamental ideas of M.Foucault, different forms of body assignment by the relations of power are investigated in the article. By the means of analysis of a disintegrated, disciplinary and erotized body a vision of evolution of body images is created in the correspondence to the history of power. The main conclusion is that a transition from a disciplinary to erotized body, as a new mean of control of human activity, is taking place.